Redefining the Broadcast Communication Model: Digital Interactivity and the Shifting Source-Receiver Relationship - ., Harliantara; Nindhasari, Harlita; Prayudha, Harlino Nandha (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The emergence of digital technologies and interactive platforms has led to fundamental changes in the dynamics of broadcast communication, requiring a re-evaluation of conventional models and a transition towards more participatory approaches. This study explores the changing source-receiver relationship in the context of digital interactivity and discusses how digital platforms have changed the traditional broadcast communication model. A systematic literature review was conducted to understand the current knowledge in this area and to identify research gaps. The findings show the growing irrelevance of linear communication models, such as the Shannon-Weaver model, in the digital age. The interactive nature of digital media has transformed passive receivers into active participants and content creators, thus blurring the boundaries between producers and consumers. This study highlights the importance of understanding communication as a networked process, through which information traverses complex social networks. The role of algorithms and personalisation in shaping media experiences is also examined, raising concerns about the fragmentation of public discourse and the creation of echo chambers. This study proposes a new theoretical framework that includes concepts, such as network communication, algorithmic communication, and participatory culture. The findings from this study can inform the design of more effective broadcast communication strategies, guide digital platform developers in creating more transparent and ethical algorithms, and assist policymakers in regulating digital media to ensure fairness and transparency.